Review of the literature on management accounting and controlling published in the journal “Controlling i Zarządzanie” from 2015 to 2022 - Roman Kotapski (Zeszyty Teoretyczne Rachunkowości, 2022)
Purpose: The aim of this article is to verify and evaluate the problems related to controlling, management accounting, and management and cost accounting, which were addressed in the issues of the journal “Controlling i Zarządzanie” (Controlling and Management) published in the period 2015–2022. Methodology/research approach: The author analyzed the published articles from the viewpoint of, among others, the problems which had been addressed, the authors of the articles, the number of the articles in respect of the existing sections of the journal regarding the areas of controlling, management accounting, management and cost accounting, the areas and types of enterprises’ activities, and the subject of their activi-ties. Findings: The issues addressed in the articles concerned a variety of subjects linked with controlling, management accounting, and management and cost accounting. The topics involved diverse aspects such as budgeting, instruments of controlling, as well as the grouping, measurement, and calculation of costs. The authors are mainly professionals such as accountants, managers, IT experts, and, less frequently, researchers, who specialize in controlling, management accounting, and cost accounting. Research limitations/implications: During the qualification of individual articles, it was not always possible to clearly assign them to separate parts, because the article could be qualified both, for example, to the controlling and management accounting part, as well as human resources. The final qualification was made subjectively by the author. Practical implications: The article presents the scope of interests of practitioners in the field of controlling, management accounting and cost accounting. It determines potential research fields and directions for future scientific research. In particular, in cooperation with representatives of business. Originality/value: The article presents a summary and a reflection on the issues dis-cussed by practitioners regarding the use of controlling, management accounting, and cost account-ing in managing a company. This is the first in-depth analysis and summary regarding this type of article to appear in a specialist publication, and that was written by both practitioners and researchers in this field in Poland.